2011
DOI: 10.1097/nen.0b013e31822830e5
|View full text |Cite
|
Sign up to set email alerts
|

Signaling of Glial Cell Line-Derived Neurotrophic Factor and Its Receptor GFRα1 Induce Nurr1 and Pitx3 to Promote Survival of Grafted Midbrain-Derived Neural Stem Cells in a Rat Model of Parkinson Disease

Abstract: Glial cell line-derived neurotrophic factor (GDNF) and its receptor GFRα1 have been implicated in the survival of ventral midbrain dopaminergic (DA) neurons, but the molecular mechanisms bywhich GDNF generates DA neurons in grafted midbrain-derived neural stem cells (mNSCs) are not understood. Midbrain-derived neural stem cells isolated from rat embryonic mesencephalon (embryonic day 12) were treated with GDNF or in combination with GFRα1 small interfering RNA. Reverse transcription-polymerase chain reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…However, this temporal difference may be accounted for by the long-lasting impact GDNF has upon GFRα1 expression and the difference in the quantities of GDNF typically infused into brain compared to the amount of soluble GFRα1 infused in this study. Normal levels of GDNF in the SN are 0.003 ng per mg protein in the rhesus monkey [48] and in the range of 0.01–0.06 ng per mg protein in the rat [19, 49], while levels of cleaved GFRα1 in the rat SN are ~100-fold greater, being 5.7 ± 0.50 ng per mg protein by our calculation (Fig. 1).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, this temporal difference may be accounted for by the long-lasting impact GDNF has upon GFRα1 expression and the difference in the quantities of GDNF typically infused into brain compared to the amount of soluble GFRα1 infused in this study. Normal levels of GDNF in the SN are 0.003 ng per mg protein in the rhesus monkey [48] and in the range of 0.01–0.06 ng per mg protein in the rat [19, 49], while levels of cleaved GFRα1 in the rat SN are ~100-fold greater, being 5.7 ± 0.50 ng per mg protein by our calculation (Fig. 1).…”
Section: Discussionmentioning
confidence: 79%
“…Notably, GDNF increases the expression of GFRα1 [20, 49] specifically within the SN up to 30 days following a 100-µg infusion of GDNF into the ipsilateral striatum [20]. This sustained elevation of nigral GFRα1 levels is seen despite the fact that nigral GDNF levels themselves are elevated at 1 day, but not 7 days, following striatal GDNF infusion [21].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, neurotrophic factors, such as Brain derived neurotrophic factor (BDNF) and glial cell line derived neurotrophic factor (GDNF), play an important role in the protection of DA neurons. They are involved in the regulation of differentiation and survival of midbrain DA neurons [30,31]. Peng et al [32] found that PITX3 overexpression in SH-SY5Y cells and primary ventral mesencephalic (VM) cultures significantly unregulated the mRNA and protein levels of both BDNF and GDNF.…”
Section: Discussionmentioning
confidence: 98%
“…Although the biological functions of bexarotene still remains to be defined, one recent study has revealed that bexarotene might have the capacity to rescue the disrupted GDNF signaling and regulate oxidative phosphorylation and Nurr1-related genes [92]. In addition, animal tests have indicated that transplantation of GDNF-pretreated NSCs could dramatically enhance the expression of Nurr1 and TH [88]. Given that GDNF has a poor blood-brain-barrier penetrating feature, GDNF inducers such as telmisartan, carcitriol, rhus verniciflua stokes and cabergoline can stimulate GDNF expression [9398].…”
Section: Prospect Of Nurr1-based Therapy For Pdmentioning
confidence: 99%